Multitasking vision language models for vehicle plate recognition with VehiclePaliGemma - Nouar AlDahoul; Myles Joshua Toledo Tan; Raghava Reddy Tera; Hezerul Abdul Karim; Chee How Lim; Manish Kumar Mishra; Yasir Zaki (Scientific Reports)
Abstract License Plate Recognition (LPR) automates vehicle identification using cameras and computer vision. It compares captured plates against databases to detect stolen vehicles, uninsured drivers, and crime suspects. Traditionally reliant on Optical Character Recognition (OCR), LPR faces challenges like noise, blurring, weather effects, and closely spaced characters, complicating accurate recognition. Existing LPR methods still require significant improvement, especially for distorted images. To fill this gap, we propose utilizing visual language models (VLMs) such as OpenAI GPT-4o (Generative Pre-trained Transformer 4 Omni), Google Gemini 1.5, Google PaliGemma (Pathways Language and Image model + Gemma model), Meta Llama (Large Language Model Meta AI) 3.2, Anthropic Claude 3.5 Sonnet, LLaVA (Large Language and Vision Assistant), NVIDIA VILA (Visual Language), and moondream2 to recognize such unclear plates with close characters. This paper evaluates the VLM’s capability to address the aforementioned problems. Additionally, we introduce “VehiclePaliGemma”, a fine-tuned Open-sourced PaliGemma VLM designed to recognize plates under challenging conditions. We compared our proposed VehiclePaliGemma with state-of-the-art methods and other VLMs using a dataset of Malaysian license plates collected under complex conditions. The results indicate that VehiclePaliGemma achieved superior performance with an accuracy of 87.6%. Moreover, it is able to predict the car’s plate at a speed of 7 frames per second using A100-80GB GPU. Finally, we explored the multitasking capability of VehiclePaliGemma model to accurately identify plates containing multiple cars of various models and colors, with plates positioned and oriented in different directions.